2008
DOI: 10.3138/ptc.60.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gait Speed in Patients after Hip Fracture

Abstract: Purpose: Following hip fracture, patients demonstrate greatly reduced walking speeds 1 year later compared with age-matched elders. The purpose of our study was to examine the factors that relate to gait speed in patients after hip fracture. Methods: Forty-two men and women (mean age 79 AE 7.5 years) who sustained a hip fracture participated in this study. Linear regression analysis was used to determine a statistical model that best predicted gait speed, the dependent variable. Gait speed was measured with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Physical function factors known to influence falls include balance function 13 and gait speed 14 . In older adults after hip fracture, age, sex, and cognitive decline have been reported as factors associated with balance function, 15 and sex, type of fracture, knee extensor strength, and cognitive decline have been reported as factors associated with gait speed 16 . The clinical question of this study is whether PHFKP development during hospitalization could be a factor influencing balance function and gait speed.…”
Section: Introductionmentioning
confidence: 89%
“…Physical function factors known to influence falls include balance function 13 and gait speed 14 . In older adults after hip fracture, age, sex, and cognitive decline have been reported as factors associated with balance function, 15 and sex, type of fracture, knee extensor strength, and cognitive decline have been reported as factors associated with gait speed 16 . The clinical question of this study is whether PHFKP development during hospitalization could be a factor influencing balance function and gait speed.…”
Section: Introductionmentioning
confidence: 89%
“…These findings add to the body of literature by providing evidence that both are predictive for both comfortable and fast gait speed. The relationship between lower extremity strength and gait speed has been demonstrated primarily using measures of dynamometry [14,18,27,28]. Specifically, knee extensor, hip extensor, and ankle plantarflexor strength have all been shown to have associations with gait speed using these methods [18,28].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, there is an overall reduction in muscle strength, leading to potential functional mobility limitations and a higher risk for falls and hospitalizations [25]. Multiple studies have identified both composite lower extremity muscle strength and individual muscle strength as predictive variables for comfortable and fast gait speeds [14,18,[26][27][28]. Aranda-Garcia (2015) found that isometric knee extensor strength was the best predictor of fast gait speed in community dwelling older adults, explaining 47.5% of the variance in both global characteristics and physical abilities models.…”
Section: Introductionmentioning
confidence: 99%